The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12882-023-03102-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic periodontitis in patients undergoing peritoneal dialysis and its correlation with peritoneal dialysis-related complications

Abstract: Objective The microinflammatory state can influence the occurrence of dialysis-related complications in dialysis patients. Chronic periodontitis (CP), in which plaque biofilm is considered to be the initiating factor, is a chronic infectious disease in the oral cavity. It is still uncertain whether CP affects the microinflammatory state in peritoneal dialysis (PD) and the occurrence of dialysis-related complications. The purpose of this study was to investigate the correlation between the perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A micro-inflammatory state refers to the process where toxins stimulate the production of various inflammatory factors, which persist in the blood, causing mild inflammation. This micro-inflammatory state is persistent low-level inflammation characterized by elevated levels of inflammatory factors [ 86 ]. Uremic toxins can directly stimulate the increase of superoxide dismutase (SOD) and reactive oxygen species (ROS), enhance lipid peroxidation, and exacerbate oxidative stress [ 87 ].…”
Section: Risk Factor Management Of Hf In Dialysis Patientsmentioning
confidence: 99%
“…A micro-inflammatory state refers to the process where toxins stimulate the production of various inflammatory factors, which persist in the blood, causing mild inflammation. This micro-inflammatory state is persistent low-level inflammation characterized by elevated levels of inflammatory factors [ 86 ]. Uremic toxins can directly stimulate the increase of superoxide dismutase (SOD) and reactive oxygen species (ROS), enhance lipid peroxidation, and exacerbate oxidative stress [ 87 ].…”
Section: Risk Factor Management Of Hf In Dialysis Patientsmentioning
confidence: 99%
“…Regarding CKD, a significant positive association between PD and CKD has been established (Deschamps‐Lenhardt et al, 2019; Nylund et al, 2018; Ruokonen et al, 2019; Shimizu et al, 2023). Moreover, PD is universally present in patients undergoing peritoneal dialysis, and the presentation of periodontitis influences their systemic inflammatory state (Chen et al, 2023). On the other hand, a previous study have found association between the prevalence of AP and patients with end‐stage renal disease (Khalighinejad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PD is universally present in patients undergoing peritoneal dialysis, and the presentation of periodontitis influences their systemic inflammatory state (Chen et al, 2023). On the other hand, a previous study have found association between the prevalence of AP and patients with end-stage renal disease (Khalighinejad et al, 2017).…”
mentioning
confidence: 99%